2021
DOI: 10.1080/21655979.2021.1995105
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of sevoflurane post-treatment alleviating hypoxic-ischemic encephalopathy by affecting histone methyltransferase G9a in rats

Abstract: Hypoxic-ischemic encephalopathy (HIE) is recognized as the main cause of neonatal death, and efficient treatment strategies remain limited. This study aims to investigate the mechanism of sevoflurane (SF) post-treatment in alleviating HIE in rats. The HIE rat model and oxygen-glucose deprivation (OGD) cell model were established, and adeno-associated virus (AAV)-histone-lysine N-methyltransferase EHMT2 (G9a) was transfected after SF treatment. The learning and memory ability and the levels of nerve growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In addition, Takashio and Tschorn et al found that plasma BDNF expression was reduced in patients with HF and associated with HF severity, suggesting that it might be a clinically valuable biomarker of HF [ 27 , 28 ]. After G9a overexpression in vitro and in vivo, the enrichment levels of H3K9me2 in the promoter region of BDNF were augmented, whereas the levels of BDNF were decreased, along with damaged neurons and impaired learning and memory abilities of rats with hypoxic-ischemic encephalopathy [ 29 ]. There findings were largely in line with our observation where enrichment of BDNF promoters by G9a and H3K9me2 was significantly reduced after silencing of G9a in H9C2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Takashio and Tschorn et al found that plasma BDNF expression was reduced in patients with HF and associated with HF severity, suggesting that it might be a clinically valuable biomarker of HF [ 27 , 28 ]. After G9a overexpression in vitro and in vivo, the enrichment levels of H3K9me2 in the promoter region of BDNF were augmented, whereas the levels of BDNF were decreased, along with damaged neurons and impaired learning and memory abilities of rats with hypoxic-ischemic encephalopathy [ 29 ]. There findings were largely in line with our observation where enrichment of BDNF promoters by G9a and H3K9me2 was significantly reduced after silencing of G9a in H9C2 cells.…”
Section: Discussionmentioning
confidence: 99%